The Effect of Counselor Training Programs on the Quality of Interventions in Schools - Omar Ahmad; Maria Clara Reyes; Usman Tariq (Journal of Loomingulisus ja Innovatsioon, 2026)
Entrepreneurial ecosystems have become critical drivers of the creative economy by fostering collaboration, innovation, and sustainable business models. In the context of the Global South, these ecosystems face structural challenges such as limited access to finance, infrastructure gaps, and unequal opportunities, yet they also present unique opportunities for inclusive growth. This study aims to examine how entrepreneurial ecosystems shape and influence the development of the creative economy in a Global South context, with a focus on the mechanisms that enable creative entrepreneurs to thrive despite these constraints. A qualitative case study design was employed, drawing on data collected from 45 semi-structured interviews with entrepreneurs, policy makers, and cultural actors, as well as document analysis and participant observation in three creative industry clusters. The findings reveal that local networks, informal mentoring, and culturally embedded innovation serve as the backbone of these ecosystems. Results highlight that while systemic limitations persist, adaptive strategies, collaborative practices, and policy interventions can strengthen ecosystem performance and contribute to creative sector resilience. This study concludes that fostering inclusive entrepreneurial ecosystems in the Global South has a transformative potential for advancing the creative economy and addressing socio-economic disparities.